An Ovol2‐Zeb1 transcriptional circuit regulates epithelial directional migration and proliferation. (9th November 2018) - Haensel, Daniel; Sun, Peng; MacLean, Adam L; Ma, Xianghui; Zhou, Yuan; Stemmler, Marc P; Brabletz, Simone; Berx, Geert; Plikus, Maksim V; Nie, Qing; Brabletz, Thomas; Dai, Xing
Abstract: Directional migration is inherently important for epithelial tissue regeneration and repair, but how it is precisely controlled and coordinated with cell proliferation is unclear. Here, we report that Ovol2, a transcriptional repressor that inhibits epithelial‐to‐mesenchymal transition (EMT), plays a crucial role in adult skin epithelial regeneration and repair. Ovol2 ‐deficient mice show compromised wound healing characterized by aberrant epidermal cell migration and proliferation, as well as delayed anagen progression characterized by defects in hair follicle matrix cell proliferation and subsequent differentiation. Epidermal keratinocytes and bulge hair follicle stem cells (Bu‐HFSCs) lacking Ovol2 fail to expand in culture and display molecular alterations consistent with enhanced EMT and reduced proliferation. Live imaging of wound explants and Bu‐HFSCs reveals increased migration speed but reduced directionality, and post‐mitotic cell cycle arrest. Remarkably, simultaneous deletion of Zeb1 encoding an EMT‐promoting factor restores directional migration to Ovol2 ‐deficient Bu‐HFSCs. Taken together, our findings highlight the important function of an Ovol2‐Zeb1 EMT‐regulatory circuit in controlling the directional migration of epithelial stem and progenitor cells to facilitate adult skin epithelial regeneration and repair. Synopsis: Efficient wound repair and hair follicle regeneration involve coordinated movements and cellular proliferation of skin epithelial cells. The EMT repressor Ovol2 has a major role in promoting directional migration and proliferation of adult epithelial cells. Ovol2 promotes adult skin wound repair by promoting directional migration and proliferation of epidermal cells. Ovol2 promotes adult hair follicle regeneration and regulates bulge stem cell directional migration and proliferation. An Ovol2‐Zeb1 transcriptional circuit governs efficient epithelial directional migration. Abstract : Efficient wound repair and hair follicle regeneration involve coordinated movements and cellular proliferation of skin epithelial cells. The EMT repressor Ovol2 has a major role in promoting directional migration and proliferation of adult epithelial cells.